2018
DOI: 10.23889/ijpds.v3i1.447
|View full text |Cite
|
Sign up to set email alerts
|

New estimates of Australia’s centenarian population

Abstract: IntroductionThe population of Australia at the very highest ages is growing rapidly, like that of many countries. But official population estimates at these ages are of lower quality than those at younger ages, a problem shared by many countries which base their population estimates on census counts. This has implications for many uses of the data, especially rates for which the estimates provide denominators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…where 𝐷 refers to cohort deaths over the last 5 years and 5 age groups. Population estimates for the latest year are then constrained to sum to the official 85+ population estimate, an adjustment which has been shown in earlier research to provide the best level of accuracy (Wilson and Terblanche 2018).…”
Section: Methodsmentioning
confidence: 99%
“…where 𝐷 refers to cohort deaths over the last 5 years and 5 age groups. Population estimates for the latest year are then constrained to sum to the official 85+ population estimate, an adjustment which has been shown in earlier research to provide the best level of accuracy (Wilson and Terblanche 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated further weaknesses exist in census migration data including in the accuracy of destination migration which is captured for infants born within the transition interval (Rees et al 2000) and for older migrants (Wilson and Terblanche 2018;Wilson 2020). In addition, age and gender profiles in census migration data for more rural and remote destinations are known to be more volatile, partly as a result of the issues above and combined with temporal unpredictability due to their relatively small populations (Peters et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[Figure 1 about here] It is unusual for analyses of migration by age and the application of model migration schedules to extend beyond ages 85 or 90. But with rapidly growing populations at the very highest ages, particularly in the nonagenarian and centenarian age groups (Robine and Cubaynes 2017;Wilson and Terblanche 2018), there is an increasing need to include these ages in models of migration age patterns and population projections. The existing model migration schedule offers two options for representing migration rates at these ages (Figure 1).…”
Section: Introductionmentioning
confidence: 99%